INCREASING MARINE TOURISM WITH MARINE SPATIAL PLANNING METHOD AND GROWTH OF MARINE ECOSYSTEM MANAGEMENT OF UNUSED MARINE AREAS - Patel, Hasanain Imtiaz Ismail; Gurning, Raja Oloan Saut (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
The current state of the art of ecosystem-based marine spatial management (EB-MSM), a new approach to ocean management that is being supported all over the world as the best means of ensuring the sustainability of marine ecosystems. It aims to sustain robust, fruitful, and resilient ecosystems that supply essential products and services while withstanding human influences. It concentrates on all interactions within a marine ecosystem, including human interactions. The most cutting-edge science and innovative methods are needed for successful implementation. Focusing on the role of marine spatial planning (MSP) in marine ecosystem management and discussing the use of MSP to manage the risks associated with geohazards and climate change. Including creation of networks of marine protected areas (MPAs), how maritime activities are distributed both spatially and temporally, flexibility in fisheries management, actions to promote coastal resilience, the restoration of vital coastal ecosystems, the establishment of buffer zones between permanent structures and the coastline, and the implementation of risk-mitigation tools like monitoring programs and warning systems. More responsive demands of coastal countries and more actively supporting the economic integration of foreign operators and tourism. Even during disputes or cancellations, innovative ideas and agreements can stimulate the economy. For instance, a third party can create jobs in sub-Saharan West Africa, while a recreation area could increase tourist in Indonesia.